2003
DOI: 10.1074/jbc.m300417200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for DNA Recognition by the Basic Region Leucine Zipper Transcription Factor CCAAT/Enhancer-binding Protein α

Abstract: CCAAT/enhancer-binding proteins (C/EBPs) are basic region leucine zipper (bZIP) transcription factors that regulate cell differentiation, growth, survival, and inflammation. To understand the molecular basis of DNA recognition by the C/EBP family we determined the xray structure of a C/EBP␣ bZIP polypeptide bound to its cognate DNA site (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 40 publications
(39 reference statements)
4
119
0
2
Order By: Relevance
“…6B). In contrast, the C/EBP␤ mutants, Y274F and L320R, which affect DNA binding and protein dimerization, respectively (55,61), decreased the GADD45␤-dependent activities of both Col10a1 and C/EBP reporters (Fig. 6, A and B).…”
Section: C/ebp␤ Threonine 235 Mutation Disrupts Its Activation By Gadmentioning
confidence: 99%
“…6B). In contrast, the C/EBP␤ mutants, Y274F and L320R, which affect DNA binding and protein dimerization, respectively (55,61), decreased the GADD45␤-dependent activities of both Col10a1 and C/EBP reporters (Fig. 6, A and B).…”
Section: C/ebp␤ Threonine 235 Mutation Disrupts Its Activation By Gadmentioning
confidence: 99%
“…In all, 35 cycles of c-Jun and G6PD amplification conditions were: 951C for 10 min; 951C for 0.5 s; 641C for 10 s; 721C for 25 s. Running the samples on 1.2% agarose gel, the PCR fragment size of 400 bps for c-Jun and 340 bps for G6PD were observed. (Miller et al, 2003). In conclusion, c-Jun binds to C/EBPa via the leucine zipper domains and prevents C/EBPa DNA binding.…”
Section: Elevated C-jun Expression In Amlmentioning
confidence: 99%
“…1A, left panel). As documented (25,26), the C/EBP␣ prefers to bind to the consensus sequence GCAAT in the promoters of its target genes. Bioinformatic analysis showed that there was such a potential C/EBP␣ binding site between Ϫ48 to Ϫ42 bp of the galectin-1 gene (Fig.…”
Section: C/ebp␣ Transcriptionally Up-regulates the Expression Of Galementioning
confidence: 99%